Understanding Legal and Religious Dimensions of Early Marriage, and HIV/AIDS Education in Indonesia - Ahmad Alif Muzakki; Dedi Rianto Rahadi; Hally Hanafiah (Lentera Ilmu Madani, 2025)
Early marriage and a lack of understanding about HIV/AIDS are critical issues that threaten the health and future of adolescents in Indonesia. This community service activity aims to measure the effectiveness of educational workshops in increasing the knowledge and awareness of students at SMPN 2 Serang Baru, Bekasi, regarding the legal and religious dimensions of early marriage and HIV/AIDS education. By combining storytelling sessions, Focus Group Discussions (FGD), interactive quizzes, reflections, and pre- and post-tests, the results of the pre- and post-test scores showed a statistically significant increase in knowledge among participants. In accordance with Law No. 16 of 2019, the health and social impacts of early marriage, as well as the transmission and prevention of HIV/AIDS, were addressed. Qualitative results from the FGDs and reflections support these findings, indicating positive changes in participants' attitudes and awareness. It is concluded that this educational workshop model, measured through pre- and post-tests, is highly effective in enhancing adolescents' knowledge about sensitive issues and can be replicated as an evidence-based intervention program in other schools